Primary cutaneous histoplasmosis developed in the penis of an immunocompetent patient - Paixão, Mauricio; Miot, Hélio Amante [UNESP]; Avancini, João; Belda Júnior, Walter (FapUNIFESP (SciELO), 2015)
A 70-year-old male presenting a 3-month history of genital painless erythematous nodules in the balanopreputial sulcus was referred to our service. Histopathological exam presented a chronic dermatitis with epithelioid granulomas and Grocott staining revealed numerous fungal structures with a suggestive morphology of Histoplasma sp. Cultures evidenced Histoplasma capsulatum var. capsulatum. Treatment with oral itraconazole led to complete remission of lesions.

A 70-year-old male presenting a 3-month history of genital painless erythematous nodules in the balanopreputial sulcus was referred to our service. Histopathological exam presented a chronic dermatitis with epithelioid granulomas and Grocott staining revealed numerous fungal structures with a suggestive morphology of Histoplasma sp. Cultures evidenced Histoplasma capsulatum var. capsulatum. Treatment with oral itraconazole led to complete remission of lesions.
Keywords: Bacterial infections and mycoses; Genital diseases, male; Genitalia, male; Histoplasmosis; Infection; Mycoses